Association between vitamin D insufficiency and adverse pregnancy outcome: global comparisons - Bener A; Al-Hamaq AO; Saleh NM (Dove Medical Press, 2013)
Abdulbari Bener,1,2 Abdulla OAA Al-Hamaq,3 Najah M Saleh4 1Department of Medical Statistics and Epidemiology, Hamad General Hospital, Doha, Qatar; 2Institute of Population Health, University of Manchester, Manchester, UK; 3Qatar Diabetic Association, Doha, Qatar; 4Department of Obstetrics and Gynecology, Women's Hospital, Doha, Qatar Background: Vitamin D insufficiency has been associated with a number of adverse pregnancy outcomes, and has been recognized as a public health concern. Aim: The objective of this study was to determine the impact of vitamin D deficiency on maternal complications like gestational diabetes mellitus (GDM), anemia, iron deficiency, and preeclampsia among pregnant women. Subjects and methods: This was a cohort study undertaken at antenatal clinics at the Women's Hospital of Hamad Medical Corporation in Doha. A total of 2,487 Arab pregnant women above 24 weeks' gestation with any maternal complication were approached, and 1,873 women (75.3%) consented to participate in the study. Data on sociodemographic and clinical characteristics by interview and biochemistry parameters were retrieved from medical records. Multivariate logistic regression analysis was performed to determine the associated risk factors. Results: Of the studied pregnant women, nearly half of them had vitamin D deficiency (48.4%). Younger women below 30 years old (43.2%, P = 0.032), housewives (65.3%, P = 0.008), and those on low monthly household incomes (QR5,000–9,999) (49.2%, P = 0.03) were significantly more likely to have lower vitamin D compared with those who had sufficient vitamin D levels. Exposure to sunlight (63.4%, P = 0.05), daily physical activity (64.4%, P = 0.05), and vitamin D supplement intake (89.7%, P < 0.001) were significantly lower in deficient pregnant women. In the study sample of pregnant women, 13.9% had GDM, 11.5% had anemia, 8.6% had iron deficiency, and 6.9% had preeclampsia. Severe vitamin D deficiency was significantly higher in pregnant women with GDM (16.5% vs 11%), anemia (17.1% vs 11%), iron deficiency (18.5% vs 11.2%), and preeclampsia (19.8% vs 11.4%) when compared to the uncomplicated group. Socioeconomic status was low in pregnant women with complications like GDM, anemia, iron deficiency, and pre-eclampsia. Pregnancy complications like GDM (52.7%), anemia (53.2%), iron deficiency (55.6%), and preeclampsia (51.9%) were higher in Qataris. Also, GDM (66.2%), anemia (66.2%), iron deficiency (68.5%), and preeclampsia (58.1%) were observed more commonly among housewives compared to working women. Obesity was significantly more common in pregnant women with GDM (41.5%) and preeclampsia (41.1%). Conclusion: The study findings revealed that maternal vitamin D deficiency in pregnancy is significantly associated with elevated risk for GDM, anemia, and preeclampsia. The risk of vitamin D deficiency was higher in Qataris, housewives and those with low monthly household income. Keywords: pregnant women, vitamin D deficiency, GDM, anemia, iron deficiency, preeclampsia